The role of Jadid theater in the development of youth spirituality - Samadova Sarvinoz Samad Qizi (Goodwood Publishing, 2025)
Purpose: This study analyzes the role of Jadid theater in nurturing spirituality and moral awareness among youth in late 19th to early 20th century Central Asia. It seeks to show how theater became a medium for education, reform, and national awakening through cultural innovation. Research methodology: The study applies a qualitative historical approach using document and literature analysis of primary and secondary sources, including plays, newspapers, and writings of Jadid intellectuals such as Behbudi, Niyozi, Avloniy, and Fitrat. Descriptive analysis is used to interpret the ideological and structural elements of their works within socio-cultural contexts. Results: The Jadid movement transformed traditional storytelling into modern theater that addressed social issues, promoted literacy, and inspired youth spirituality. Despite censorship and scarce resources, amateur and professional groups sustained the movement, gradually expanding participation, including women. Theater became a powerful cultural tool that left a lasting legacy in Central Asian society. Conclusions: Jadid theater functioned not merely as art but as a cultural instrument combining education, morality, and national identity. By integrating traditional and modern forms, it fostered youth engagement, advanced literacy, and mobilized society toward reform, underscoring the importance of cultural platforms for social and spiritual development. Limitations: This research is limited to historical and document-based analysis, without empirical data such as interviews or reception studies that could provide contemporary perspectives. Contribution: The study enriches understanding of how Jadid theater became a strategic platform for youth spiritual development and national awakening in Central Asia.